The aim of this study was to evaluate dynamic modulus of elasticity (MOEdyn) of woods after tested those natural durability. Field tests by grave yard test were applied to prove the natural durability of jackfruit and mangium woods in ground contact. The method of non-destructive testing based on ultrasonic wave propagation was carried out to define ultrasonic velocity than that used for evaluating MOEdyn. The result showed that ultrasonic velocity of jackfruit and mangium woods decreased 3% and - Lina KARLINASARI; Ina RITA; Istie Sekartining RAHAYU (Departemen Hasil Hutan, IPB, 2009)
The aim of this study was to evaluate dynamic modulus of elasticity (MOEdyn) of woods after tested those natural durability. Field tests by grave yard test were applied to prove the natural durability of jackfruit and mangium woods in ground contact. The method of non-destructive testing based on ultrasonic wave propagation was carried out to define ultrasonic velocity than that used for evaluating MOEdyn. The result showed that ultrasonic velocity of jackfruit and mangium woods decreased 3% and 0.5%, respectively after field test. There was a significant difference of MOEdyn value between before and after natural durability testings